Networking, collaboration, and home brewing: An exploratory study. Issue 1 (2nd January 2018) - Duarte Alonso, Abel; Alexander, Nevil; O'Brien, Seamus
Abstract : This exploratory study contributes to the academic leisure literature, examining perceived benefits from and barriers to networking and collaboration among home brewers, employing social exchange theory (SET) and the theory of collaboration (TOCL). Sharing basic knowledge of recipes, camaraderie, and mutual support in home brewing activities were main perceived benefits, and lack of time and geographic isolation challenges of networking. Quality improvements, gains in strategic knowledge, and learning alongside others were key beneficial outcomes from collaboration; again, lack of time, and perceptions of giving more than receiving from collaboration, were main perceived challenges. Alignments between various tenets of the theories and the findings were revealed, for instance, concerning value, reward, outcome and transaction (SET), stakeholders of a problem domain and interactive process (TOCL). The study will discuss practical and theoretical implications that could be considered in and guide future leisure studies; in addition, new research avenues will be suggested.